Exploration of basis set issues for calculation of intermolecular interactions and density functional theory calculations of vanadium oxide clusters and their reactions with sulfur dioxide - Jakubikova, Elena, author; Bernstein, Elliot R., advisor; Rappé, Anthony K., advisor; Dorhout, P. K., committee member; Strauss, S. H., committee member; Dandy, D. S., committee member (Colorado State University. Libraries, 2007)
The ab initio calculation of intermolecular interactions requires a large basis set in order to describe systems with dominant dispersion interaction accurately. This work focuses on calculation of intermolecular bonding energies of weakly bound systems within the supermolecular method and on issues related to the choice of a basis set for these calculations, in particular size of the basis set, efficiency of 2-electron integral codes, basis set superposition error (BSSE), and the linear dependence of basis functions. In an attempt to find more efficient basis sets for calculations of intermolecular interactions, standard basis sets (10s Huzinaga, 6-311G**, cc-pV6Z), or their parts, are extended (tessellated) by a set of off-centered, s or p functions, symmetrically placed around the nuclei. Standard basis sets (10s Huzinaga, 6-311G**, cc-pVXZ, aug-ccpVXZ, X = D, T, Q, 5, 6) are also augmented by sets of atom-centered, higher angular momentum functions (p, d, f). Distance from the nucleus of tessellating functions and orbital exponents of tessellating and augmenting functions are optimized with respect to the BSSE-corrected bonding energy at the MP2 or UCCSD level of theory. The two 2 approaches are tested on the model systems with dominant dispersion interactions 3H2, (CH4)2, and Ne2 and their efficiency is compared. Both tessellation and augmentation are successful in describing the intermolecular interactions of these model systems, with augmentation being more efficient. Our results draw attention to the linear dependence problems inevitably present in accurate calculations and confirm the need for underlying standard basis sets that provide good descriptions of core and valence electrons in order for the tessellation and augmentation approaches to be reliable. Vanadium oxide is a catalytic system that plays an important role in the conversion of sulfur dioxide to sulfur trioxide. Density functional theory is employed to study structure and stability of small neutral vanadium oxide clusters in the gas phase. BPW91/LANL2DZ level of theory is used to obtain structures of VOy (y=1,...,5), V2Oy (y=2,...,7), V3Oy (y=4,...,9), and V4Oy (y=7,...,12) clusters. Energies of growth and fragmentation reactions of the lowest energy isomers of vanadium oxide molecules are also obtained to study the stability of neutral vanadium oxide species under oxygen saturated gas phase conditions. Our results suggest that cyclic and cage like structures are preferred for the lowest energy isomers of neutral vanadium oxide clusters, and oxygen-oxygen bonds are present for oxygen rich clusters. Clusters with an odd number of vanadium atoms tend to have low spin ground states, while clusters with even number of vanadium atoms have a variety of spin multiplicities for their ground electronic state. VO2, V2O5, V3O7, and V4O10 are predicted to be the most stable neutral clusters under the oxygen saturated conditions. Thermodynamics of reactions of vanadium oxide clusters with SO2 is also studied. BPW91/LANL2DZ is insufficient to properly describe relative V-O and S-O bond strengths of vanadium and sulfur oxides. Calibration of theoretical results with experimental data is necessary to compute reliable enthalpy changes for reactions between VxOy and SO2. Theoretical results indicate SO2 to SO conversion occurs for oxygen-deficient clusters and SO2 to SO3 conversion occurs for oxygen-rich clusters. Some possible mechanisms for SO3 formation and catalyst regeneration for condensed phase are also suggested. These results are in agreement with, and complement, previous gas phase experimental studies of neutral vanadium oxide clusters.
Keywords: chemistry; physical chemistry